On the importance of the bullet jacket during the penetration process: reversed-ballistic experimental and numerical study - Lesmana, Denny; Arifurrahman, Faizal; Hameed, Amer; Appleby-Thomas, Gareth J.; Santosa, Sigit P. (Springer, 2020)
The behaviour of exposed and copper-jacketed 12.7 mm En8 steel cores impacting against 5 and 9 mm Armox Advance plates was investigated to determine the significance of the jacket during the penetration. The target plates were accelerated into stationary projectiles (a reversed-ballistic configuration) and the impact was monitored using a multichannel flash X-ray system to gain insight into the interaction of the core target. Numerical simulations were also carried out to compare result with the experimental testing. Explicit numerical software LS-DYNA was used to model the behaviour of the target and the projectile during the impact collision. Fragments of the core and target plate were collected post-shot for analysis. A similar penetration behaviour was observed for both plates, although the post-shot core was shorter after impacting against the 9 mm plate, consistent with enhanced erosion behaviour. The copper jacket protected the core, resulting in greater surface defeat and dwell compared to the unjacketed core. Numerical studies agreed on the cases of projectile impacting the 5 mm and 9 mm target. However, the target fracture cannot be captured. This could be caused by the input of material data and strain rate parameter modelling in LS-DYNA was limited, while the impact phenomenon was high velocity impact that the material exhibits a highstrain rate effect. Overall, the ductile jacket appeared to serve two functions: (1) Absorbing reflected energy during impact, hence cushioning the impact and thereby preserving the core, and (2) constraining or confining the core. In this study, the steel core design and copper jacket has a more complex geometry compared to the simplified steel core designs often applied in several earlier ballistic studies. The captured flash X-rays revealed significantly less erosion in the jacketed cores, agreeing with the post-impact core length measurements.
Keywords: 12.7 mm armour piercing; Armox Advance; Gas guns; Copper jacket; Reverse ballistic; High strain rate